Hyperglycemia enhances group B Streptococcus pathogenicity by impairing TLR2 expression and chemotactic response in the human placenta - Jiménez-Escutia, Rodrigo; Villafuerte-Pérez, Arumi; Vargas-Alcantar, Donovan; Martínez-Garfias, Karina; Rodríguez-Flores, Samara; Velázquez-Sánchez, Pilar; Fortanel-Fonseca, Amaury; Zamora-Escudero, Rodrigo; Islas-López, Marcela; Mancilla-Herrera, Ismael; Díaz, Lorenza; Zaga-Clavellina, Verónica; et al. (Frontiers in Immunology, 2025)
IntroductionElevated glucose levels during pregnancy disrupt placental structure, signaling, and cellular interactions, impairing its immune response. In mothers with gestational diabetes mellitus (GDM), Streptococcus agalactiae (Group B Streptococcus, GBS) is the second leading cause of bacterial infections. GDM is also linked to altered chemokine profiles in maternal serum and placenta tissue. However, the impact of hyperglycemia on placental immune responses to bacterial infections remains poorly understood. This work aimed to evaluate cytokine and chemokine production, as well as chemotactic responses, in the placenta following GBS infection under hyperglycemic conditions.MethodsHuman villous explants from term, normoevolutive pregnancies were cultured with 5, 10 or 50 mM glucose, and subsequently infected or not with GBS. Bacterial growth and adherence to villous tissue, syncytial disruption, cytokine and chemokine mRNA expression and secretion, leukocyte chemotaxis using intervillous blood mononuclear cells (IVMC), and TLR-2 expression at both mRNA and protein levels, were evaluated.ResultsUnder high glucose conditions, GBS showed increased proliferation and invasiveness, while villous explants presented evidence of syncytial barrier degradation. Also, placental TNF-α, MCP-1, and MIP-1β were induced by GBS infection. However, the dual challenge of high glucose and infection reduced the above inflammatory markers’ gene and protein synthesis. GBS infection enhanced IVMC migration compared to uninfected groups, but the combination of GBS and hyperglycemia led to a reduced migration of IVMC, particularly monocytes and NK cells. TLR-2 placental expression was also downregulated by this dual challenge.ConclusionAt the placental level, hyperglycemia attenuates the immune response against GBS infection, promoting syncytial disruption, bacterial growth, and tissue colonization. The combined stimulus of hyperglycemia and GBS resulted in reduced placental expression of TLR-2, TNF-α, MCP-1, and MIP-1β, thereby impairing the chemotaxis of IVMC, monocytes, and NK cells. This dysregulated immune response may compromise bacterial clearance and placental integrity, favoring pathogen persistence. Our findings suggest a potential mechanism by which hyperglycemia increases susceptibility to GBS-associated complications, offering novel insight into the interplay between metabolic and infectious stressors at the maternal-fetal interface.